2014
DOI: 10.1117/12.2050686
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the thermal effects on LWIR optical designs utilizing different infrared optical materials

Abstract: The growing demand for lower cost infrared sensors and cameras has focused attention on the need for low cost optics for the long wave and mid-wave infrared region. The thermal properties of chalcogenides provide benefits for optical and optomechanical designers for the athermalization of lens assemblies as compared to Germanium, Zinc Selenide and other more common infrared materials. This investigation reviews typical infrared materials' thermal performance and the effects of temperature on the optical perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The refractive index of Ge material is 4.003 and the refractive index of ZnSe material is 2.403 [11]. Thus, one can conclude that the permissible manufacturing error of a ZnSe-material cubic phase mask is approximately 2.14 times as large as that of a Ge-material cubic phase mask.…”
Section: Our Athermalized Infrared Imaging Systemmentioning
confidence: 91%
“…The refractive index of Ge material is 4.003 and the refractive index of ZnSe material is 2.403 [11]. Thus, one can conclude that the permissible manufacturing error of a ZnSe-material cubic phase mask is approximately 2.14 times as large as that of a Ge-material cubic phase mask.…”
Section: Our Athermalized Infrared Imaging Systemmentioning
confidence: 91%
“…It has been shown in a previous paper by the present authors that first-order approximations in athermalization theory are inadequate for accurately determining the practical performance impact of the material thermal constant. 6 In that study, a singlet was designed in several LWIR materials (including As 40 Se 60 and Ge 28 Sb 12 Se 60 ) and the MTF sensitivity to operating temperature was determined. Though these differences in MTF performance did not match first-order theory, they were still significant in differentiating lens materials for use in LWIR imaging systems.…”
Section: Thermal Design Studymentioning
confidence: 99%
“…The singlet design case study found that As 40 Se 60 was approximately half as sensitive to temperature as Ge 28 Sb 12 Se 60 . 6 In this paper, we seek to extend that design study to the case of 2-element lens systems. Because there are many more design forms possible for a 2-element system, we began with a nominal design survey to determine the design forms that were least sensitive to tolerances for a given set of constant performance constraints.…”
Section: Thermal Design Studymentioning
confidence: 99%